Impact of Different Concentrations of Cinnamon Essential Oil onThe Physico-Chemical, Microbiological, and Sensory Characteristicsof Refrigerated Pork Sausages - Mounika, D; Rao, B Eswara; Babji, Y; Ambedkar, Y R; Rao, T Srinivasa (Journal of Meat Science, 2024)
The investigation examined the impact of varying concentrations of Cinnamon Essential Oil (CEO) on the preservation of pork sausages. The sausages were divided into different groups: a control group,0.2 µl/g CEO (T1) 0.4 µl/g CEO (T2) and 0.6% µl/g (T3). All these samples were stored at 4°C for 15 days. Notably, the sausages treated with 0.4 µl/g CEO exhibited superior preservation qualities, as evidenced by lower levels of TBARS, free fatty acids, pH, water activity, microbial count (Total Plate Count, coliform count and staphylococcal count) and sensory properties (colour, flavour and overall acceptability) compared to all other treatments (p<0.05). So it can be concluded that the addition of 0.4 µl/g CEO had the most effective preservative impact on pork sausages during the refrigerated storage for a period of 15 days.